Irving Penn - Centennial - Penn, Irving 1917-2009; Hambourg, Maria Morris 1949-; Rosenheim, Jeff L. (The Metropolitan Museum of Art, 2018)
"Celebrating the centennial of Irving Penn's birth, this volume spans the entirety of his groundbreaking career. The introduction situates his work in the context of the various artistic, social, and political environments and events that affected the content of his photographs. The essays acquaint readers with Penn's primary subjects and campaigns, including early documentary scenes and imagery; portraits; fashion; female nudes; people of Peru, Dahomey (Benin), New Guinea, and Morocco; still lifes; and more"--Provided by publisher
This catalogue is published in conjunction with 'Irving Penn: Centennial', on view at The Metropolitan Museum of Art, New York, from April 20 through July 30, 2017; at the Grand Palais, Paris, from September 21, 2017, through January 29, 2018; at C/O Berlin, from March 24 through July 1, 2018; and at the Instituto Moreira Salles, São Paulo, from August 21 through November 25, 2018.
Keywords: Penn, Irving / Exhibitions; Penn, Irving -- 1917-2009; Geschichte 1939-2007; Geschichte 1948-2007; Photography, Artistic / Exhibitions; Aktfotografie; Fotografie; Mensch -- Motiv; Porträtfotografie; Mode; Photographie; Portraits; Ausstellungskatalog; Ausstellungskatalog -- Grand Palais -- 21.09.2017-29.01.2018 -- Paris; Ausstellungskatalog -- Instituto Moreira Salles -- Herbst 2018 -- São Paulo; Ausstellungskatalog -- Metropolitan Museum of Art -- 20.04.2017-30.07.2017 -- New York, NY; Bildband